The general features of tropical Sumatra Squalls. (1st July 2016) - Lo, Jeff Chun‐Fung; Orton, Thomas
Abstract : Sumatra Squalls are common weather phenomena which have a very large impact affecting 85 million people throughout equatorial South East Asia, and many more through trade links with other regions; however, current comprehension behind Sumatra Squalls is not well studied and interpretation is insufficient. The aim of this article is to raise the community interest on Sumatra Squalls and underline the need for increased research. Twenty‐two years of observational data has been collated and analysed to create climatologically general features of Sumatra Squalls. These squalls have a clear diurnal cycle and commonly make landfall in the west coast of the Malay Peninsula and Singapore during the pre‐dawn and early morning. Additionally, these squalls commonly form during the intermonsoon season (April‐May and October‐November) and Southwest monsoon (June‐September) seasons with average frequencies of 8 and 6 occurrences per month respectively.